IMPLEMENTATION ANALYSIS OF TRIAL BALANCE WORKSHEET PREPARATION USING ATLAS AT KAP AGUS DEWANTO - Farizki, Flouren Apta Ditza; hasanah, uswatun (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
The application of digital technology in the audit field has transformed the way auditors manageand prepare audit working papers, particularly the Trial Balance worksheet, which serves as theprimary reference for subsequent audit stages. This study is a descriptive qualitative research basedon internship activities conducted at a public accounting firm and aims to analyze theimplementation of Trial Balance worksheet preparation using the ATLAS (Audit Tool and LinkedArchive System) application at KAP Agus Dewanto. Data were collected through directobservation and informal discussions with auditors to understand the workflow, system utilization,and challenges encountered in practice. The results show that ATLAS assists auditors throughautomated data processing, standardized worksheet formats, and integration with other auditcomponents such as lead schedules and adjustment journals, thereby reducing manual errors,improving documentation efficiency, and maintaining data consistency throughout the auditprocess. However, several challenges remain, particularly related to user adaptation and accuracyin initial data entry. Overall, the implementation of ATLAS improves the accuracy and efficiencyof audit working paper preparation and supports more structured audit documentation.